(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Introduction- Tennallur is the prehistoric site. There is Siva temple Katcikoduta Nayanar by his name. This temple was renovated by the Chola, the Pandya and the local chieftains. According to the mythology the God of this place blessed one lady by her physiology appearance. Hence the name is of this Lord is Katcikoduta Nayanar. Now the original temple for fully damage and the sculptures are scattered here and there. The local people collected this sculptures and displayed in a particular place and worshiping them. The ancient stones of this temple are collected and utilized to construct is Mariyamman temple. It is called as Tennallur Mariyamman temple. Bull taming (Jallikkattu) is the famous festival conducted every year with seven different vaadivasal (Gate).